2008
DOI: 10.16910/jemr.2.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Eye Tracking Analysis in Reading Online Newspapers

Abstract: Reading online newspapers is increasingly becoming more common, so that thousands of newspapers are published online today. Despite this development, there are many unanswered questions concerning subjects’ behaviour during reading an online newspapers. Recording eye movements when a subject is navigating within a news website can provide quantitative and objective information on subject’s behaviour and combined with other methodologies – usability testing, focus groups, log analysis - represents a powerful to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…An important lesson learned was that the position of ad banners affects the way users look at them (the best location being the left column). Other interesting research includes the works by Holmqvist et al (2003) and Zambarbieri et al (2008), both focused on the way online newspapers are read. Recently Ferreira et al (2011) examined the impact of verbal emotional cues in capturing attention on advertising regions of a news portal.…”
Section: Previous Workmentioning
confidence: 99%
“…An important lesson learned was that the position of ad banners affects the way users look at them (the best location being the left column). Other interesting research includes the works by Holmqvist et al (2003) and Zambarbieri et al (2008), both focused on the way online newspapers are read. Recently Ferreira et al (2011) examined the impact of verbal emotional cues in capturing attention on advertising regions of a news portal.…”
Section: Previous Workmentioning
confidence: 99%
“…Solamente cuatro de los estudios están basados en experimentación directa con usuarios: Zambarbieri et al (2008) utilizan el método de rastreo ocular en la lectura (eye tracking) aplicado a periódicos italianos; Aranyi et al, (2012) basan su trabajo en pruebas psicométricas en sitios de noticias; mientras que Yu y Kong (2016) realizan test A/B sobre navegación web en pantallas pequeñas.…”
Section: Métodos Y Herramientasunclassified
“…Tal es el caso del comercio electrónico, la educación, la sanidad, el gobierno, el turismo o los medios de comunicación (Pedraza-Jiménez et al, 2016). Ejemplos de estos últimos instrumentos de evaluación de calidad web focalizados en cibermedios encontramos en trabajos pioneros como los de Abdullah y Wei (2008), basado en heurísticas de usabilidad; Zambarbieri et al (2008), que aplica la técnica de eyetracking o seguimiento ocular; Rodríguez-Martínez et al (2010), análisis experto destinado a analizar la adopción de la Web 2.0; Al-Radaideh et al (2011), sustentado en el estudio de usuarios; Chung et al (2012), sobre la base de encuestas; o el protocolo de análisis de contenidos propuesto por Martins (2012).…”
Section: Introductionunclassified
“…Much more research has been devoted to multimodal stimuli from sources other than digital media (Kurzhals, Fisher, Burch, & Weiskopf, 2016). Studies have found that verbal cues tend to receive more attention than images on billboards (Grigaliūnaitė et al, 2016;Zantides & Kourdis, 2014), newspapers (Holsanova, Rahm, & Holmqvist, 2006), stories in online newspapers (Zambarbieri, Carniglia, & Robino, 2008), or when simple images and simple verbal texts are combined (Arndt, Schüler, & Scheiter, 2015). All these studies suggest that texts receive more visual fixations, regardless of the size, color, place, and nature of images.…”
Section: Multimodal Stimulimentioning
confidence: 99%